The effect of race/ethnicity on cancer-specific mortality after salvage radical prostatectomy - Wenzel, Mike; Würnschimmel, Christoph; Nocera, Luigi; Colla Ruvolo, Claudia; Hoeh, Benedikt; Tian, Zhe; Shariat, Shahrokh F; Saad, Fred; Briganti, Alberto; Graefen, Markus; Preisser, Felix; Becker, Andreas; et al. (Frontiers in oncology, 2022)
BACKGROUND: To test the effect of race/ethnicity on cancer-specific mortality (CSM) after salvage radical prostatectomy (SRP). MATERIAL AND METHODS: We relied on the Surveillance, Epidemiology and End Results database (SEER, 2004-2016) to identify SRP patients of all race/ethnicity background. Univariate and multivariate Cox regression models addressed CSM according to race/ethnicity. RESULTS: Of 426 assessable SRP patients, Caucasians accounted for 299 (69.9%) vs. 68 (15.9%) African-Americans vs. 39 (9.1%) Hispanics vs. 20 (4.7%) Asians. At diagnosis, African-Americans (64 years) were younger than Caucasians (66 years), but not younger than Hispanics (66 years) and Asians (67 years). PSA at diagnosis was significantly higher in African-Americans (13.2 ng/ml), Hispanics (13.0 ng/ml), and Asians (12.2 ng/ml) than in Caucasians (7.8 ng/ml, p = 0.01). Moreover, the distribution of African-Americans (10.3%-36.6%) and Hispanics (0%-15.8%) varied according to SEER region. The 10-year CSM was 46.5% in African-Americans vs. 22.4% in Caucasians vs. 15.4% in Hispanics vs. 15.0% in Asians. After multivariate adjustment (for age, clinical T stage, lymph node dissection status), African-American race/ethnicity was an independent predictor of higher CSM (HR: 2.2, p < 0.01), but not Hispanic or Asian race/ethnicity. The independent effect of African-American race/ethnicity did not persist after further adjustment for PSA. CONCLUSION: African-Americans treated with SRP are at higher risk of CSM than other racial/ethnic groups and also exhibited the highest baseline PSA. The independent effect of African-American race/ethnicity on higher CSM no longer applies after PSA adjustment since higher PSA represents a distinguishing feature in African-American patients.
Keywords: salvage radical prostatectomy; prostate cancer; post-radiotherapy recurrence; race; cancer specific survival; ethnicity